Analisis Tingkat Kesehatan Bank dengan Menggunakan Metode Risk Profile, Good Coorporate Governance, Earning, & Capital (RGEC) terhadap Bank Umum Syariah yang Terdaftar di OJK Periode 2019-2022: Studi Kasus Perusahaan Perbankan Syariah Yang Terdaftar di Otoritas Jasa Keuangan - Sucipto, Moch Cahyo; Suryana, Eka Ahadiyat; Nuraidah, Siti Iwa (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2025)
The role of banks in today's society is so important, banks must be able to survive in every condition that occurs. Assessment of the Soundness Level of Sharia Commercial Banks with provisions for capital adequacy, asset quality, management quality, liquidity, profitability and solvency, as well as other aspects related to business and the obligation to carry out business activities in accordance with the precautionary principle. The main indicator used as the basis for bank health research is the financial reports of Islamic commercial banks which do not yet show the bank's overall financial condition. Then, risk management begins with the awareness that risk cannot be avoided or eliminated but is controlled by assessing the health level of Islamic commercial banks. The aim of this research is to find out the health level of sharia commercial banks registered with the financial services authority (OJK) for the 2019-2022 period as measured using the RGEC method, and to find out the health level of sharia commercial banks. This type of research is descriptive quantitative with research subjects at Sharia Commercial Banks registered with the Financial Services Authority (OJK) for the period 2019 - 2022. The data in this research uses secondary data in the form of financial reports. The sampling technique uses purposive sampling. The analysis technique used is bank health analysis with a risk approach (Risk-based Bank Rating) with assessment coverage based on Risk Profile, Good Corporate Governance, Earning and Capital (RGEC) factors. The research results show that the health level of PT. Bank Aceh Syariah, for the 2019-2022 period as measured by the RGEC method (Risk Profile, Good Corporate Governance, Earnings, & Capital) as a whole is included in Composite Rank 1 (PK-1), reflecting the bank's condition which is generally "Very Healthy" , so it is considered very capable of facing significant negative assumptions from changes in business conditions and other external factors. Then PT. BPD Riau Kepri Syariah, and PT. Bank Muamalat Indonesia Tbk for the 2019-2022 period as measured using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital) as a whole can be said to be included in Composite Rank 2 (PK-2), reflecting the condition of the bank which is generally "Healthy ”. The conclusion shows that the condition of the 3 Islamic commercial banks is that 1 bank is categorized as very healthy and 2 banks are categorized as healthy, but overall, the average percentage of the 3 Islamic commercial banks is in the "Very Healthy" category based on the bank health ratio calculation.